Molecular Characterization of High-Level Gentamicin Resistance in Enterococcal Isolates from Clinical Samples in South India - Dr. J. Vijay Anand; Dr. Nalayini Samidurai; Dr. S. Mahesh Prabhu, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: High-level gentamicin resistance (HLGR) in Enterococci compromises the synergistic efficacy of aminoglycosides combined with cell wall-active antibiotics, creating significant treatment challenges. Objective: To determine the prevalence of HLGR phenotypically and to characterize the underlying resistance genes in Enterococcus isolates from clinical specimens at a tertiary care center in South India. Methods: A total of 104 Enterococcus isolates were tested for HLGR using the Kirby-Bauer disc diffusion method with high-concentration gentamicin discs. PCR assays were performed on HLGR isolates to detect aminoglycoside resistance genes: aac(6’)-Ie-aph(2”)-Ia, aph(2”)-Ib, aph(2”)-Ic, and aph(2”)-Id. Results: HLGR was observed in 64 (61.5%) isolates. Molecular analysis revealed that all HLGR isolates harbored the bifunctional aminoglycoside-modifying enzyme gene aac(6’)-Ie-aph(2”)-Ia. None of the isolates carried aph(2”)-Ib, aph(2”)-Ic, or aph(2”)-Id genes. Conclusion: The aac(6’)-Ie-aph(2”)-Ia gene is the predominant mechanism of HLGR among Enterococcus isolates in this region. Routine molecular screening for this gene is recommended to enhance antimicrobial resistance surveillance and guide effective therapeutic and infection control strategies.